2014 UK national guideline for the management of anogenital herpes. (October 2015) - Patel, Raj; Green, John; Clarke, Emily; Seneviratne, Kanchana; Abbt, Naomi; Evans, Ceri; Bickford, Jane; Nicholson, Marian; O'Farrell, Nigel; Barton, Simon; FitzGerald, Mark; Foley, Elizabeth
These guidelines concern the management of anogenital herpes simplex virus infections in adults and give advice on diagnosis, management, and counselling of patients. This guideline replaces the 2007 BASHH herpes guidelines and includes new sections on herpes proctitis, key points to cover with patients regarding transmission and removal of advice on the management of HSV in pregnancy which now has a separate joint BASHH/RCOG guideline.